Pengaruh Pemberian Minuman Herbal Bunga Telang (Clitoria Ternatea) dan Jahe (Zingiberofficinale) Terhadap Hipertensi Lansia Perempuan di Puskesmas Delatope - Sari, Putri Mayang; Nurdiana, Nurdiana; Imansari, Adillah (Lembaga Penerbitan Unversitas Esa Unggul, 2025)
Hypertension is a common health issue among the elderly, with prevalence increasing with age. Preliminary studies indicate that herbal drinks made from butterfly pea flower (Clitoria ternatea) and ginger (Zingiber officinale) may help lower blood pressure. This study aims to assess the effect of herbal drinks based on these ingredients on lowering blood pressure in elderly women with hypertension at Delatope Health Center, Banawa Tengah District. This research employs a quantitative approach with a pre-experimental design using a one-group pretest and posttest strategy. The population consists of elderly women with hypertension registered at Delatope Health Center, aged 60 and above. A purposive sampling technique was used, with a sample size of 16 respondents collected in May 2025. Data were gathered through blood pressure measurement using a sphygmomanometer, and data analysis was conducted using a paired t-test. Before the intervention, the majority of respondents had moderate hypertension (160/100 mmHg) at 56.25%. After the intervention, the average blood pressure decreased to 140/90 mmHg, with 43.75% classified as having mild hypertension. The results indicate that the herbal drink significantly reduced bloodpressure (p = 0.000). There is a significant effect of the herbal drink made from butterfly pea flower and ginger on lowering blood pressure in elderly women with hypertension. It is recommended that Delatope Health Center develop community-based educational programs for the elderly regarding the use of herbal plants, specifically butterfly pea and ginger, as a non-pharmacological therapy, including hygienic and effective preparation methods.